Pengelolaan Sarana dan Prasarana Penjas Di Sekolah Dasar Se-Kecamatan Mijen (Universitas Negeri Semarang, 2022)
Some elementary school physical education teachers in Mijen District have not been optimal in teaching due to limited facilities and infrastructure. So that teaching and learning activities have not run optimally. Thus, what is the process of managing physical education infrastructure in elementary schools in order to maximize physical education teaching and learning activities? This data collection uses qualitative methods, with source triangulation techniques. Based on the results of research conducted in several aspects, the management of elementary school physical education infrastructure is quite good, such as planning, procurement, use, inventory, and elimination. However, there are some schools in use that are not in accordance with their functions due to limitations, and have not yet recorded. For the maintenance of physical education infrastructure in all schools is classified as very lacking, because the school does not have a structured schedule for the maintenance of facilities and infrastructure. It can be concluded that the management of physical education infrastructure in elementary schools in The Mijen District, the city of Semarang is quite good, but there are several aspects in the management of infrastructure in elementary schools in the Mijen Regency that must be improved or improved.